2015
DOI: 10.3109/1354750x.2015.1118541
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of oxidative-stress and inflammation in exhaled breath condensate from hospital cleaners

Abstract: Professional exposure to chlorinated agents increases EBC biomarkers of oxidative stress and inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Three studies investigating FeNO in exhaled breath condensate after acute (preshift versus postshift) exposure to cleaning products containing chlorine did not found a significant difference between cleaners and controls. 44 46 48 Of note, in one of them, a positive association of exposure to cleaning products with biomarkers of oxidative stress and inflammation (ie, malondialdehyde (MDA), 4-hydroxynonenal (4-HNE), nitrates (NO3-), in the exhaled breath condensate was found 48 (table 3).…”
Section: Other Health Outcomesmentioning
confidence: 99%
“…Three studies investigating FeNO in exhaled breath condensate after acute (preshift versus postshift) exposure to cleaning products containing chlorine did not found a significant difference between cleaners and controls. 44 46 48 Of note, in one of them, a positive association of exposure to cleaning products with biomarkers of oxidative stress and inflammation (ie, malondialdehyde (MDA), 4-hydroxynonenal (4-HNE), nitrates (NO3-), in the exhaled breath condensate was found 48 (table 3).…”
Section: Other Health Outcomesmentioning
confidence: 99%
“…Oxidative stress has been suggested as one of the mechanisms for the impact of inhaled irritant cleaning products on the airway epithelium [44,59]. In accordance with this hypothesis, an Italian study of hospital cleaners reported that potential biomarkers of oxidative stress in exhaled breath condensate were higher in cleaners compared to control workers, while Fractional exhaled Nitric Oxide levels were similar in both groups [47].…”
Section: Mechanismsmentioning
confidence: 82%
“…Irritant-induced asthma or rhinitis can be caused by a single high level (accidental) exposure to irritants or by chronic, lower level ('daily-life') exposure to irritants [30,45,46]. Chronic exposure to inhaled irritants from DCPs may cause injury of the airway epithelium, oxidative stress and neutrophilic airway inflammation [47][48][49], which are also relevant to COPD pathogenesis. Among all cleaning agents reported as likely causative agents of occupational asthma in THOR surveillance network, 15 low molecular weight organic compounds were identified [13].…”
Section: Mechanismsmentioning
confidence: 99%
“…Nitrate and nitrite anions have been considered by a number of researchers as stable metabolites of nitric oxide and are present in living organisms in micromolar amounts [ 58 ]. In addition, a different, but a significant amount of these ions comes from food and water.…”
Section: Introductionmentioning
confidence: 99%